2007
DOI: 10.1111/j.1365-2133.2007.08273.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and aetiology of basal cell carcinoma

Abstract: Basal cell carcinoma (BCC) is a malignant epithelial neoplasm of the skin preferentially affecting male caucasians and is rarely observed in patients with more intense skin pigmentation. A characteristic feature of BCCs are their extremely low risk to metastasize. Epidemiological data indicate that the overall incidence is increasing worldwide significantly by about 3-10% per annum.(1-3) Based on the increasing incidence of this usually not life-threatening tumour BCC appears to develop into a growing public h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
178
3
28

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(214 citation statements)
references
References 61 publications
(107 reference statements)
5
178
3
28
Order By: Relevance
“…[14][15][16][17] In most studies, male sex is reported as predominant, however in our patients the opposite was observed. 6,8,16,18 BCC represented over two thirds of all NMSC and predominated over SCC on all skin areas, except for the lower lip and the genital area. In the former, SCC predominance is probably explained by its particular anatomic disposition, nearly perpendicular to the solar radiation, potentiating the effect of UV light.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16][17] In most studies, male sex is reported as predominant, however in our patients the opposite was observed. 6,8,16,18 BCC represented over two thirds of all NMSC and predominated over SCC on all skin areas, except for the lower lip and the genital area. In the former, SCC predominance is probably explained by its particular anatomic disposition, nearly perpendicular to the solar radiation, potentiating the effect of UV light.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,5 Multiple risk factors have been described for NMSC, but chronic exposure to ultraviolet radiation, particularly UV-B, is clearly the most important, progressively inducing keratinocyte carcinogenesis and resulting in BCC or SCC after several years or decades of cumulative cellular degeneration. 2,3,6,7,8 However, BCC and SCC do not arise randomly in a chronically sun-exposed skin as the pattern of UV exposure seems to play a role: many studies have shown that SCC is frequently associated with long term chronic UV-exposure, while BCC is associated with intense intermittent UV-exposure. 2,5,6 The reason why these two patterns of sun-exposure seem to act differently in the skin has not been identified yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological data (5,6,8,9,(11)(12)(13)(14)(15)(16) show clearly that ultraviolet (UV) radiation, particularly UVB, is an essential etiological factor in the carcinogenesis of skin tumors. UV exposure is a chronic oxidative stress (17) that causes DNA damage with specific mutations of suppressor genes such as p53 (14,16,(18)(19)(20)(21)(22): it is activated along with telomerase (23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Its cumulative risk in the Caucasian population is over 30% and its incidence has been increasing worldwide at an annual rate of 3-7%, constituting a public health issue. 1,2 The reasons for this increase in frequency are yet to be fully clarified; however, they may involve the increased awareness of the population regarding the condition and improvements in the training of professionals to establish diagnosis at earlier stages; longer unprotected exposure to ultraviolet radiation and more leisure time; a culture that idealizes tanned skin; depletion of the ozone layer; increased longevity and the consequent proportional rise in the elderly segment of the population. 3 The treatment of choice continues to be surgical removal of the lesion, which also facilitates the retrieval of computerized data from pathology services, enabling these data to be correlated with demographic indicators and with the demands on the healthcare system.…”
Section: ©2011 By Anais Brasileiros De Dermatologiamentioning
confidence: 99%